The Evaluation Of Endoplasmic Reticulum Stress Among Regular Kratom Users And Its Implications For Kratom Dependence And Kratom Induced Depressive Symptoms - Yang, Bin (2024)
Recent research showed that psychoactive substances can induce endoplasmic reticulum (ER) stress and unfolded protein response (UPR). This case-control study filled the research gap by: (1) determining the association between kratom use characteristics (such as the age of first kratom use, the duration of kratom use, the average frequency and quantity of daily kratom use, and the time since last kratom consumption prior to blood collection for analysis) and the mRNA and protein expression of ER stress sensors; and (2) assessing the correlations between the mRNA and protein expression of ER stress sensors and severity of kratom dependence and kratom induced depressive symptoms during kratom abstinence.